Concentration and market power in the Philippine manufacturing industry - Aldaba, Rafaelita M. (2003)
This paper looks at the presence of barriers to competition that prevent domestic and international prices from converging. These barriers may dampen, even reverse the gains from trade liberalization. Three decades of protectionism and import substitution in the Philippines have led to high levels of industrial concentration in a few wealthy families and small groups. Most of all, the experience has led to the deterioration of the culture of competition in the country. While liberalization may be a precondition for the growth of a free market, it does not, by itself, guarantee effective competition. For effective competition to emerge, trade reforms must be accompanied by the creation of competitive market and industry structures. The transition from import substitution to a more open economy requires not only the rule of law, but efficient institutions to support growth and institutional change.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 56-57)
Keywords: Competition, Unfair -- Philippines; Manufacturing industries -- Philippines; Trade liberalization -- Philippines; Restraint of trade